Proposed upgrading and new design scheme of Mama Restaurant for Mama Adunan Entrerprise at No 6699, Jalan Sultanah, 05350 Alor Setar / Siti Fatimah Jaafar - Jaafar, Siti Fatimah (Faculty of Architecture, Planning and Surveying, 2010)
Propose Upgrading and New Design Scheme of MAMA Restaurant for Mama Adunan Enterprise. Is proposed for a new image to its interior and to appeal the corporate image. Recently the restaurant started with a small business at shop lot. Day by day this business more attraction from customer until the owner have a own building to running their business and also have a new branch. Therefore the upgrading needs to occurs to make it easier for the customer to have an impression of Modern Kedah Traditional restaurant and also to offer comfort to the customer. The concept has to relate to Traditional of Kedah so that it can communicate directly to the customer. The interior flow has to proper in its organization so that the staff and customer circulation is divided. By executing this project, the client hopes to attract more tourist and the feel comfortable when they attend and dine in the restaurant and they can experience the Kedah traditional environment and culture.